2009
DOI: 10.1111/j.1365-2222.2009.03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Timothy grass pollen major allergen Phl p 1 activates respiratory epithelial cells by a non‐protease mechanism

Abstract: We conclude that under physiological conditions Phl p 1 affects tracheal epithelial cells through a non-proteolytic activity. Enhancement of TGF-beta expression induced by Phl p 1 together with the increased release of IL-6 and IL-8 might provide an indirect mechanism through which the allergen may cross the epithelial barrier and attracts immunocompetent cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…Thus, microarray analysis revealed that Timothy grass pollen extract induces elevation of IL-8 expression in NCI-H292 cells, a mucoepidermoid carcinoma cell line derived from human lungs [25]. Human airway epithelial cell secrete IL-8 following incubation timothy grass pollen allergen [26], and this IL-8 secretion in bronchial epithelial cells from not only subjects with uncontrolled asthma, but healthy volunteers [27]. Allergenic pollens have intrinsic NADPH oxidases, and these NADPH oxidases raised oxidized glutathione (GSSG) and 4-hydroxynonenal (4-HNE) in BAL fluids of challenged mice.…”
Section: Pollen Allergenic Extracts Stimulate Cxcl Chemokines and Recmentioning
confidence: 99%
“…Thus, microarray analysis revealed that Timothy grass pollen extract induces elevation of IL-8 expression in NCI-H292 cells, a mucoepidermoid carcinoma cell line derived from human lungs [25]. Human airway epithelial cell secrete IL-8 following incubation timothy grass pollen allergen [26], and this IL-8 secretion in bronchial epithelial cells from not only subjects with uncontrolled asthma, but healthy volunteers [27]. Allergenic pollens have intrinsic NADPH oxidases, and these NADPH oxidases raised oxidized glutathione (GSSG) and 4-hydroxynonenal (4-HNE) in BAL fluids of challenged mice.…”
Section: Pollen Allergenic Extracts Stimulate Cxcl Chemokines and Recmentioning
confidence: 99%
“…Remarkably, pathogenesis of birch pollen allergy was associated with the hypo-responsiveness of EC derived from allergic donors [73]. Natural purified major timothy grass pollen allergen Phl p 1 was able to induce pro-inflammatory cytokines secretion from alveolar A549 cells [74]. The authors excluded any proteolytic activity and speculated the induction of TGF-ß and p38 MAPK to have an indirect effect on epithelial integrity.…”
Section: Interaction Of Non-proteases With Ecmentioning
confidence: 99%
“…Interleukin-8 is a major neutrophil chemoattract chemokine. Phl p 1 induces interleukin-8 secretion from human airway epithelial cells independently of its protease activity [46]. Likewise, timothy grass pollen extracts induce interleukin-8 secretion in bronchial epithelial cells from healthy volunteers and patients with severe asthma [31].…”
Section: Innate Immune Responses Induced By Pollen Extractsmentioning
confidence: 99%